Avaliação da disponibilidade de água em aquíferos por meio de análises espaço-temporais - Brito Neto, Romildo Toscano de (2012)
Increasing groundwater extraction for domestic, agricultural, and industrial supply frequently makes exploitation exceed the natural recharge rate. This results in decreasing volumes, deteriorating water quality, and soil degradation. The goal of this study is to assess water availability in the Texas State (USA) portion of the Ogallala aquifer, where extraction has reached levels that are above the recharge values. Fifty three years of water level data from wells between 1960 and 2012 were used. Fifty three surfaces each were created using both (kriging and spline techniques) of spatial interpolation, and cross-validation methods (leaveone- out, and holdout) were used to compare the predicted water level surfaces with the well data. The predictions were similar and the results were satisfactory, however we found spline technique simpler, and easier for automatic processing of multiple surfaces, and we recommend it. However, kriging technique presents higher accuracy. After processing the water level surfaces; the saturated thickness and volume (pixel by pixel), for the whole time series were estimated. This allowed temporal analysis to be performed from the results. A set of 492 water level variation time series (to analyze trends using the Mann-Kendall test) were selected and grouped by cluster analysis (using both hierarchical and k-means methods). From the temporal analyses, the spatial distribution of the results was verified, and it was observed that the clusters most likely to decrease converge with the critical areas identified. Furthermore, the influence of agricultural activities on water level variance was established, showing a strong relationship between the two. Finally, the results showed that over 53 years, the total water volume had been reduced by 33.9%. A full 74.39% of the time series analyzed also showed a decreasing trend in water levels, and it was observed that the saturated thickness is gradually being reduced as well